Effect of Standardized Warfarin Treatment Protocol on Anticoagulant Effect: Comparison of a Warfarin Medication Therapy Adherence Clinic with Usual Medical Care - Aidit, Salihah; Soh, Yee Chang; Yap, Chuan Seng; Khan, Tahir M.; Neoh, Chin Fen; Shaharuddin, Shazwani; Kassab, Yaman W.; Patel, Rahul P.; Ming, Long C. (Frontiers in Pharmacology, 2017)
Objective: The main objective of this study was to evaluate the impact of pharmacist-led warfarin management and standardised treatment protocol. Methods: A retrospective cohort study was carried out in a cardiology referral hospital located in central Kuala Lumpur, Malaysia, from 2009 to 2014. The inclusion criteria were: adult patients who were diagnosed and treated for atrial fibrillation (AF) with warfarin, attended the warfarin medication therapy adherence clinic (WMTAC) for at least 12 weeks, and with at least 4 INR readings. The electronic medical records were reviewed for demographics, type of AF, warfarin dose, INRs, adverse events, co-morbidities and drug-drug interactions. The outcome measures included the mean time to therapeutic INR, the mean percentage of time in therapeutic range (TTR), bleeding events, and common drug interactions. Results: Out of 473 patients, 151 patients fulfilled the inclusion criteria. The findings revealed that there were significant associations between the usual medical care group and pharmacist-led WMTAC in terms of TTR (p=0.01) and INR (p=0.02) levels. A positive impact of pharmacists’ involvement in the WMTAC clinic was where the 'pharmacist's recommendation accepted' (p=0.01) and “expanded therapeutic INR range” (p = 0.04) were statistically significantly higher in the WMTAC group. Conclusions: There is a significant positive association between the pharmacist-led WMTAC and anticoagulation effect (therapeutic TTR, INR). The identified findings show that expanded role of pharmacist in pharmacist-managed warfarin therapy is beneficial to optimize the warfarin therapy. This study also highlights the critical roles that pharmacists can actively play to ensure optimal anticoagulation pharmaceutical care.